An empirical calibration of the helium abundance in H ii regions based in literature and CALIFA survey data. Issue 4 (17th June 2021) - Valerdi, M; Barrera-Ballesteros, J K; Sánchez, S F; Espinosa-Ponce, C; Carigi, L; Mejía-Narváez, A
ABSTRACT: Helium is the second most common chemical species in the Universe. The study of helium abundance has the potential to unravel the chemical evolution of and within galaxies. In this study, we provide an empirical calibration for the singly ionized helium abundance: 12 + log10 (He + /H + ), based on the emission line flux ratio Heλ5876 /H  α from Galactic and extragalactic H ii regions compiled from the literature. Based on this calibrator, we explore for the first time the helium abundance in a large sample of H ii regions located in galaxies representative of the nearby Universe from the CALIFA survey. Furthermore, this calibrator allows us to explore the variations of the helium abundance with respect to the oxygen abundance. The observed trends are in agreement with a change in the chemical enrichment with mass/oxygen abundance similar to the one observed due to the inside-out model in a MW-galaxy (highlighting the connection between resolved and global trends in galaxies). Our calibrator provides an empirical proxy to estimate the helium abundance at kpc scales as well as to constrain chemical evolutionary models.